Incidencia de la destrucción de hábitat del mono aullador por causa de la deforestación en la comunidad Tablada de Sánchez del cantón Chone - Zambrano Vite, Paul Alexander (2022)
The objective of this research was to demonstrate the impact on the howler monkey habitat due to deforestation in the Tablada De Sánchez community of the Chone canton, focused on determining the main causes of deforestation, the composition of the groups, the description of their behavior and characteristics of existing vegetation. In the investigation, 28 hectares, distributed in three farms, were evaluated, in addition, a 280-hour sampling was carried out, identifying three groups of howler monkeys. In the study period, 3 foraging routes were determined, which have differences in their physical characteristics due to the disturbance of the area and the minimum floristic diversity, likewise, they had a daily trajectory with an average of 50 m. The trees with the highest use were the medium ones (-15 m) with 59% because they are the most branched and abundant in the study area, and the tall trees (+15m) are used by 40%. It was observed that the behavior of primates is flexible and this has helped them to survive under strong pressure from humans, such as the deforestation of their habitat, which is why they are found in small groups and remnant spaces. Finally, the owners of the farms accept and are willing to participate in training programs on conservation and management of forest areas where monkeys live and to include these spaces in reforestation and conservation programs.